Solve the given equations 4x – 19y +13 = 0, 13x – 23y = –19.
Answer
Verified
510.6k+ views
Hint: Solving the equations means, we have to find the values of the variable in the given equations. We can use the substitution method to find the variables.
Complete step-by-step answer:
The given equations are
$4x - 19y + 13 = 0$ .... (1)
$13x - 23y = - 19$ .... (2)
From equation (2) we get x value as $x = \dfrac{{23y - 19}}{{13}}$
Substituting this x value in equation (1), we get
$4\left( {\dfrac{{23y - 19}}{{13}}} \right) - 19y + 13 = 0$
Multiplying the above equation with 13 on both sides,
$ \Rightarrow 4 \times 13\left( {\dfrac{{23y - 19}}{{13}}} \right) - 19 \times 13y + 13 \times 13 = 0 \times 13$
On simplification,
$$\eqalign{
& \Rightarrow 4\left( {23y - 19} \right) - 247y + 169 = 0 \cr
& \Rightarrow \left( {92y - 76} \right) - 247y + 169 = 0 \cr
& \Rightarrow - 155y + 93 = 0 \cr
& \Rightarrow 155y = 93 \cr
& \Rightarrow y = \dfrac{{93}}{{155}} = \dfrac{3}{5} \cr} $$
Substituting this ‘y’ value in equation (2) to get ‘x’ value,
$ \Rightarrow 13x - 23\left( {\dfrac{3}{5}} \right) = - 19$
Simplifying the above equation,
$\eqalign{
& \Rightarrow 13x = - 19 + \dfrac{{69}}{5} \cr
& \Rightarrow 13x = \dfrac{{ - 26}}{5} \cr
& \Rightarrow x = \dfrac{{ - 26}}{{5 \times 13}} \cr
& \Rightarrow x = \dfrac{{ - 2}}{5} \cr} $
$\therefore $ The solution of given equations is $x = \dfrac{{ - 2}}{5},y = \dfrac{3}{5}$
Note: We have to change one equation completely into a one variable equation with the help of the second equation. Then we will get the value of one variable, we can substitute that value in any of the previous equations to get the value of the remaining variable.
Complete step-by-step answer:
The given equations are
$4x - 19y + 13 = 0$ .... (1)
$13x - 23y = - 19$ .... (2)
From equation (2) we get x value as $x = \dfrac{{23y - 19}}{{13}}$
Substituting this x value in equation (1), we get
$4\left( {\dfrac{{23y - 19}}{{13}}} \right) - 19y + 13 = 0$
Multiplying the above equation with 13 on both sides,
$ \Rightarrow 4 \times 13\left( {\dfrac{{23y - 19}}{{13}}} \right) - 19 \times 13y + 13 \times 13 = 0 \times 13$
On simplification,
$$\eqalign{
& \Rightarrow 4\left( {23y - 19} \right) - 247y + 169 = 0 \cr
& \Rightarrow \left( {92y - 76} \right) - 247y + 169 = 0 \cr
& \Rightarrow - 155y + 93 = 0 \cr
& \Rightarrow 155y = 93 \cr
& \Rightarrow y = \dfrac{{93}}{{155}} = \dfrac{3}{5} \cr} $$
Substituting this ‘y’ value in equation (2) to get ‘x’ value,
$ \Rightarrow 13x - 23\left( {\dfrac{3}{5}} \right) = - 19$
Simplifying the above equation,
$\eqalign{
& \Rightarrow 13x = - 19 + \dfrac{{69}}{5} \cr
& \Rightarrow 13x = \dfrac{{ - 26}}{5} \cr
& \Rightarrow x = \dfrac{{ - 26}}{{5 \times 13}} \cr
& \Rightarrow x = \dfrac{{ - 2}}{5} \cr} $
$\therefore $ The solution of given equations is $x = \dfrac{{ - 2}}{5},y = \dfrac{3}{5}$
Note: We have to change one equation completely into a one variable equation with the help of the second equation. Then we will get the value of one variable, we can substitute that value in any of the previous equations to get the value of the remaining variable.
Recently Updated Pages
Glucose when reduced with HI and red Phosphorus gives class 11 chemistry CBSE
The highest possible oxidation states of Uranium and class 11 chemistry CBSE
Find the value of x if the mode of the following data class 11 maths CBSE
Which of the following can be used in the Friedel Crafts class 11 chemistry CBSE
A sphere of mass 40 kg is attracted by a second sphere class 11 physics CBSE
Statement I Reactivity of aluminium decreases when class 11 chemistry CBSE
Trending doubts
10 examples of friction in our daily life
Difference Between Prokaryotic Cells and Eukaryotic Cells
One Metric ton is equal to kg A 10000 B 1000 C 100 class 11 physics CBSE
State and prove Bernoullis theorem class 11 physics CBSE
What organs are located on the left side of your body class 11 biology CBSE
Define least count of vernier callipers How do you class 11 physics CBSE